2014
DOI: 10.1097/ico.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Successful Müller Muscle–Conjunctiva Resection in Patients With Boston Keratoprosthesis Type I

Abstract: This retrospective case series describes 7 eyes with KPros that underwent successful MMCR without compromise to the integrity of the KPro. Because these patients are at high risk for potential complications, we recommend careful patient selection, a goal of undercorrection, and consideration of supplemental procedures to the lower eyelids to minimize complications to the KPro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Furthermore, lower lid laxity may negatively affect the corneal graft. 5 In our study, MMCR±T, combined with lateral tarsal strip procedure, was performed in 2 patients with eyelid laxity to improve the BCL position for adequate coverage of the corneal graft.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, lower lid laxity may negatively affect the corneal graft. 5 In our study, MMCR±T, combined with lateral tarsal strip procedure, was performed in 2 patients with eyelid laxity to improve the BCL position for adequate coverage of the corneal graft.…”
Section: Discussionmentioning
confidence: 95%
“…Eyelid ptosis may decrease the visual acuity and visual field that was improved with PK. 5,6 The main goal in these patients are to improve their vision and quality of life. The second goal is to achieve a satisfactory upper eyelid height and symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another high‐risk group for ocular surface compromise are patients with previous keratoprosthesis type 1. A small study assessed the outcomes of seven patients with KPro undergoing MMCR surgery, and found that none of the patients had complications, or any compromise to the conjunctival or donor cornea …”
Section: Can Posterior Approach Ptosis Surgery Be Used In High Risk Pmentioning
confidence: 99%
“…A small study assessed the outcomes of seven patients with KPro undergoing MMCR surgery, and found that none of the patients had complications, or any compromise to the conjunctival or donor cornea. 45 Mueller's muscle resection also appears to give good results for ptosis in the anophthalmic socket, 46 and it has been reported to be able to treat both giant fornix syndrome and ptosis in the anophthalmic socket simultaneously. 47 Whilst to the authors best knowledge, there are no studies in the literature regarding the use of ptosis surgery, specifically posterior ptosis surgery, in patients with cicatrizing conjunctival disease, the authors feel that a history of cicatrizing conjunctival disease is a true contra-indication to posterior approach ptosis surgery.…”
Section: Can Posterior Approach Ptosis Surgery Be Used In High Riskmentioning
confidence: 99%